A new water-soluble ruthenium(II) carbonyl complex: cis-[Ru(bpy)2(SO3)(CO)]. (15th July 2019) - de Sousa, Aurideia P.; do Nascimento, Juliana S.; Ayala, Alejandro Pedro; Bezerra, Beatriz Pinheiro; Sousa, Eduardo H.S.; Lopes, Luiz G.F.; Holanda, Alda K.M.
Graphical abstract: A new CO-bound ruthenium complex, cis- [Ru(bpy)2 (SO3 )(CO)], was prepared and characterized. This compound has shown to be air stable, water soluble and capable to release CO after irradiation with UV light ( λ irr.  = 300, 350 or 395 nm). The high solubility in water at physiological (pH 7.4) makes this compound a suitable option for biological use. Abstract: The interest in therapeutical applications of carbon monoxide to physiological targets has led us to explore CO releasing molecules (CORM's), particularly those that decomposes upon a specific stimuli, i.e. light irradiation. Here, we prepared a photoactivated, air stable and water soluble ruthenium(II) complex, cis- [Ru(bpy)2 (SO3 )(CO)], which releases carbon monoxide upon light irradiation. Indeed, many CORMs face very limited water solubility calling for improving this drawback. Photolysis of this complex using UV light in aqueous solution leads to high quantum yield of a single CO release. The release of CO was confirmed by myoglobin assay, and a careful monitoring of this photo-reaction was performed using HPLC. Our results showed it might serves as a carbon monoxide releasing moiety, which can be induced photochemically. Despite the lack of pharmacological and toxicological studies, these results are quite encouraging and might eventually lead this compound to become a relevant pharmacological agent.